Just cities and nature-based solutions in the Global South: A diagnostic approach to move beyond panaceas in Brazil. Issue 143 (May 2023) - Torres, Pedro Henrique Campello; Souza, Daniele Tubino Pante de; Momm, Sandra; Travassos, Luciana; Picarelli, Sophia B.N.; Jacobi, Pedro Roberto; da Silva Moreno, Robson
Abstract: Within the context of climate change and the quest for more sustainable cities, greener urban solutions are gaining traction through emerging concepts that have been orienting municipalities' regeneration and development agendas, including the so-called nature-based solutions (NbS), which have been discussed, planned, and proposed worldwide by academics, NGOs, and policymakers. Comprising different scales and typologies, NbS makes up a modern toolkit of actions towards decarbonized, climate-resilient, and ecologically healthy cities, claiming ample ecological, social, and economic benefits. A literature analysis indicates a greater presence of research and projects focused on NbS in countries in the Global North than in the South; however, given their accelerated urban growth, lack of green areas, and degradation of local environments, cities of the South urgently need such solutions. Nonetheless, research on the effects of urban greening agendas in the Global North has demonstrated that solutions may be entangled with neoliberal practices of space production that exacerbate inequalities, resulting in harmful social impacts such as displacement of people and increases in land and housing costs. This study seeks to build an anticipatory understanding of practices that articulate NbS in the Global South from a Brazilian viewpoint. Given Brazil's reality of social and environmental injustices, we focus on whether implementing NbS could amplify such problems. Our objective is to contribute to the debate by (1) understanding how the NbS concept is being appropriated, in practice, in Brazil, and (2) reflecting and pointing out paths and recommendations on how to plan NbS through a justice lens. Highlights: Nature-based solutions (NbS) are spreading rapidly in the Global North. Empirical work on NbS and the dimensions of justice in the Global South is lacking. Environmental justice policy and planning are absent from Brazil's NbS projects. We identify possible undesired social impacts of NbS and preventive measures. There is a need to include "developing a Just City" as a goal in the planning axis.